Economic reform and coping with the economic crisis in the Iraqi Kurdistan Region ( 2014 –2017): Challenges and prospects - Kamran Ahmad Hama; Niaz Nijmedin Nouri (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This study sheds light on the causes of economic crisis in the Kurdistan Region of Iraq during (2014-2018). First, it explores the roles of economic ideas, economic policies, and structural imbalances in creating the financial crisis and recession. Second, it focuses on the Kurdistan Region's case, with paying a particular attention to the economic policies of KRG in deepening the recent crisis. The study also focuses on oil-rich countries and the programs proposed by IMF and the World Bank for economic reform in the developing countries, explaining where these programs may not fit the economic conditions in the Kurdistan Region. The last section devotes to show alternative programs for economic reform in the Region. The study supports the analysis by using formal data and descriptive explanations.